Marginal and internal fit of zirconia based fixed dental prostheses fabricated with different concepts - Florian Beuer; Natalie Korczynski; Antonia Rezac; et al (Dove Medical Press, 2010)
Florian Beuer1, Natalie Korczynski1, Antonia Rezac1, Michael Naumann2, Wolfgang Gernet1, John A Sorensen31Department of Prosthodontics, Ludwig-Maximilians University, Munich, Germany; 2Department of Prosthodontics and Material Sciences, University of Ulm, Germany; 3Pacific Dental Institute, Portland, Oregon, USAAbstract: The purpose of this in vitro study was to compare the precision of fit of substructures milled from semi-sintered zirconia blocks, fabricated with two different fabrication concepts. Three-unit, posterior fixed dental prostheses (FDP) were fabricated for standardized dies (n = 10) with the laboratory Computer Aided Design (CAD)/Computer Aided Manufacturing (CAM) system Cercon® Brain (Brain) and the centralized CAD/CAM system Compartis Integrated Systems (Compartis). After cementation to the dies, the FDP were embedded and sectioned. Four cross-sections were made of each abutment tooth, and marginal and internal fit were evaluated under an optical microscope. A one-way analysis of variance (ANOVA) was used to compare data (α = 0.05). Mean gap dimensions at the marginal opening for Brain and Compartis were 56.0 (±34.5) μm and 51.7 (±45.2) μm, respectively. Mean internal gap dimensions of 62.8 (±37.5) μm to 164.6 (±33.4) μm were measured depending on the measurement location and the fabrication concept. Mean marginal openings and internal adaptations were not significantly different for both systems. Three out of four measurement locations showed significantly different cement gaps. Within the limitations of this study, the results suggest that the accuracy of both investigated systems is satisfactory for clinical use. The laboratory fabrication exhibited similar accuracy as the centralized manufacturing.Keywords: zirconia, CAD/CAM, fit, FDP, all-ceramic